Developing Model of Automated Dormitory Management System Using Waterfall Approach to Enhance Efficiency and Minimize Human Error - Paskarina, Chastin Sugmala; Harefa, El Edo Suyono; Tenggono, Alfred (International Journal of Informatics and Computation, 2026)
Dormitory management commonly relies on manual procedures for scheduling cleaning duties, monitoring cleaning supplies, verifying task completion, and supervising resident activities. These processes often lead to inefficiencies, inconsistent data management, and limited coordination among dormitory stakeholders. This paper presents an Automated Dormitory Management System (ADMS) that digitalizes dormitory operations through a centralized platform. The system integrates automated cleaning duty scheduling, supply monitoring, duty report submission, and administrative supervision while utilizing the Waterfall software development model for system development. Firebase Real-Time Database and Firebase Storage are employed to provide secure data management and real-time synchronization across multiple user roles. Functional testing was conducted to evaluate the performance of each module for Residents, Floor Leaders, and Dormitory Directors. The results demonstrate that the automated scheduling module successfully generates balanced cleaning assignments, synchronizes schedules in real time, and correctly implements role-based access control. The supply monitoring module accurately updates inventory information with immediate synchronization, while the duty reporting module reliably stores photographic evidence and reports data. Furthermore, the administrative dashboard effectively consolidates weekly operational reports, inventory status, and resident information into a centralized monitoring interface. Therefore, the proposed system satisfies all functional requirements and improves operational efficiency, transparency, accountability, and coordination in dormitory management through integrated real-time cloud services.